THE INFLUENCE CHURCH SERVICES ON THE CHARACTER YOUNG CHRISTIANS IN TANGERANG REGENCY - Simarmata, Harold Vidian Exaudi; Pratama, Samuel Indra; Veronica, Stevani (Jurnal Profesi Bimbingan dan Konseling, 2024)
Church services play a significant role in shaping a person's character, particularly that of the younger Christian age. The environment that young Christians grow and develop in has a profound impact on their character development. In addition to being a place of worship, the church serves as a spiritual home where people can apply religious teachings, values, and principles to everyday life. The purpose of this study is to ascertain how church services affect young Christians' development of character in Tangerang Regency. There was quantitative analysis in this study. In order to collect data, questionnaires were distributed and respondents were provided with a number of written statements. Teenage Christian and Catholic residents of Tangerang Regency were the respondents who were asked to complete the questionnaire utilizing the scale filling method with Google Form media. With a 51% coefficient of determination, this study shows that church service has a major influence on how Christian youth in Tangerang develop as individuals. An study of the data revealed a considerable correlation between youth involvement in church ministry and their moral growth, sense of responsibility, and assimilation of Jesus Christ's teachings. The study's practical consequences highlight the crucial role that church ministries play as environments for Christian religious education that support the development of moral principles and values in line with Christian teachings. The potential for the development of models or frameworks that can enhance theoretical and practical understanding in this area is presented, along with recommendations for future research that include more in-depth contextual considerations within the Tangerang community and more investigation of particular factors that influence character formation .